Asia-Pacific Regional Consultation on Plant Genetic Resources, 27-29 November 1996, New Delhi, India - Arora, R.K.; Riley, K.W.; International Plant Genetic Resources Institute (1998)
The Asia-Pacific Regional Consultation was held at the Indian Agricultural Research Institute (IARI), New Delhi, India from 27-29 November 1996. It was organized by IPGRI in collaboration with FAO, IARI and ICAR. This was the first Regional Consultation after the fourth International Technical Conference on Plant Genetic Resources held at Leipzig, Germany in June 1996. Globally, much information has been synthesized on PGR for food and agriculture in the FAO State of the World's Plant Genetic Resources and the Global Plan of Action for the conservation and sustainable utilization of plant genetic resources for food and agriculture. It discussed the concerns and issues emerging out of the deliberations of the ITC, the sub-regional meetings held in Beijing for East Asia, and at Bangkok for South, South-East Asia and the Pacific; and follow up action required to further strengthen PGR collaboration regionally and sub-regionally within Asia-Pacific. The scientific agenda was discussed in four sessions. Session I deliberated upon the 'Analysis of recent fora from an Asia-Pacific perspective'; Session II on the 'Status of PGR networks in Asia/Pacific'; Session III dealt with the 'Key issues on (a) Conservation and use of PGR, and (b) Farmers' Rights and Benefit sharing'; and the last session IV, on the 'Mechanisms for regional collaboration'. The participants, after the deliberations of these four sessions, were grouped into two groups for drafting the recommendations. Group I dealt with the main PGR issues that related to conservation and utilization of PGR and policy issues linked with these. The Group II dealt with the mechanism for germplasm conservation and exchange. These suggestions/recommendations were discussed in Session V (Plenary Session) by all the participants and finalized. Major emphasis was as follows: · Need to realize the value of PGR and sustaining PGR activities. · Need to strike a balance between food security and environmental conservation including PGR conservation, improvement and utilization. · Need to link conservation and improvement activities with the utilization of PGR. · Need for policy on PGR issues, mechanisms for promoting partnership/collaboration in the region and to enhance Human Resource Development. Major emphasis was on regional, sub-regional and national activities. Prioritization on the nature and extent of PGR activities was focussed on the following.